2013
DOI: 10.1002/nau.22533
|View full text |Cite
|
Sign up to set email alerts
|

The minimum important difference for the International consultation on incontinence questionnaire-Urinary incontinence short form in women with stress urinary incontinence

Abstract: Introduction Minimum important difference (MID) estimates the minimum degree of change in an instrument's score that correlates with a patient's subjective sense of improvement. We aimed to determine the MID for the International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form (ICIQ-UI SF) using both anchor based and distribution based methods derived using data from the Trial of Midurethral Slings (TOMUS). Materials and Methods Instruments for the anchor-based analyses included th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 14 publications
0
43
1
1
Order By: Relevance
“…The MIDs for the ICIQ-UI are reported on either women with only stress incontinence, or on women of all ages. 18, 19 The mean length of treatment for the women in this study was 61 days, a full month short of the 4 month time frame to reach the MIDs the ICIQ-UI reported in the literature 18, 19 In clinical practice, the length of treatment of women undergoing physical therapy interventions for incontinence varies based on a wide range of factors possibly including ability to pay for treatment, insurance coverage, and stopping treatment before the intervention is completed. The discrepancies between populations, age groups, and time frames for comparing the MIDs and MCDs to the length of treatment in our population may explain why the MID and MCDs were not attained by our group.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The MIDs for the ICIQ-UI are reported on either women with only stress incontinence, or on women of all ages. 18, 19 The mean length of treatment for the women in this study was 61 days, a full month short of the 4 month time frame to reach the MIDs the ICIQ-UI reported in the literature 18, 19 In clinical practice, the length of treatment of women undergoing physical therapy interventions for incontinence varies based on a wide range of factors possibly including ability to pay for treatment, insurance coverage, and stopping treatment before the intervention is completed. The discrepancies between populations, age groups, and time frames for comparing the MIDs and MCDs to the length of treatment in our population may explain why the MID and MCDs were not attained by our group.…”
Section: Discussionmentioning
confidence: 80%
“…The score ranges from 0 to 21 with greater scores indicative of increased symptom severity and impact 12 . The ICIQ-UI demonstrates good construct validity and reliability 17 The minimum important difference (MID) for the ICIQ-UI was reported to be a decrease by 5 points at 12 months and decrease by 4 points at 24 months by Sirls in 2015 18 . Nystrom reported the MID for a population of adult women with stress incontinence to be a decrease by 2.52 points at 4 months 19 .…”
Section: Methodsmentioning
confidence: 99%
“…The clear discrepancy between MCID in the above studies shows that more research is needed in this area. Nyström et al hypothesized that PGI-I outcome may be better correlated with postoperative ICIQ-SF score than the change in the score over time which was clearly lower than that found by Sirls et al [10]. …”
Section: Discussionmentioning
confidence: 83%
“…The minimal detectable change (MDC) and minimally clinically important difference (MCID) after intervention for UI are not yet established, but there has been initial investigation in this area [510]. Sirls et al assessed 597 women in the TOMUS RCT and found that the minimum important difference (MID) for the ICIQ-SF in a population of women with stress-predominant UI is −5 for assessment at 12 months and −4 for assessment at 24 months [10]. They concluded that MID may be overestimated in surgical cohorts because of uniformly high preoperative scores without significant variability that show a large improvement after treatment [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation